2017
DOI: 10.1051/matecconf/20179506006
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Multi-Body Dynamics Simulation for the Conveyor Chain Drive System

Abstract: Abstract. The conveyor chain drive system which included four sprockets, four flat bars (chain guides) and one conveyor chain had been assembled into commercial software, MSC.ADAMS. The conveyor chain was connected with rollers for running on the chain guides. The multi-body dynamics (MBD) simulation was implemented to study the large displacement of chain components which happened during rotations of the symmetric model of the conveyor chain drive system. The physical experiment had obtained by construction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The authors found that the order of reliability of the vibration system from high to low is lignite, coking coal, anthracite, and gangue when the scraper chain system transmits different materials. Suvanjumrat et al [20] used multibody dynamic simulation method to study the large displacement of the chain parts during rotation in the symmetric model. The validity of the simulation model is verified by comparing the MBD simulation and the physical experiment of the conveyor chain drive system.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the order of reliability of the vibration system from high to low is lignite, coking coal, anthracite, and gangue when the scraper chain system transmits different materials. Suvanjumrat et al [20] used multibody dynamic simulation method to study the large displacement of the chain parts during rotation in the symmetric model. The validity of the simulation model is verified by comparing the MBD simulation and the physical experiment of the conveyor chain drive system.…”
Section: Introductionmentioning
confidence: 99%